Honor as Property - Bond, Johanna (Columbia Journal of Gender and Law, 2012)
This Article is the first to use a property lens to explore the social construction of honor within legal systems around the world. The Article makes the claim that the law in many countries has implicitly treated honor as a form of property and has made legal and social allowances for men who seek to reclaim honor property through violence. The Article expands the boundaries of the existing scholarship concerning honor-related violence by exploring the intersections between social constructions of honor and social constructions of property. Using a property lens to analyze the relationship between honor, patriarchal control, and law provides a deeper understanding of the motivations for this form of gender-based violence. The Article also assesses the implications of this new theoretical model and concludes that honor must be reframed to position women as potential holders of honor property and to disassociate honor from the social regulation of women’s sexuality.